In ruins - Woodward, Christopher (Pantheon Books, 2001)
"We live in a world of relentless progress, and yet we cannot pull ourselves away from the enchantment of what once was: the hold that an abandoned building can exert on us, the spell cast by the remains of past settlement. In Ruins is a meditation on ruins and, most particularly, a history of our fascination with them." "When we contemplate ruins, Woodward suggests, we contemplate the prospect of the future. Ruins are also the jigsaw pieces of what once was, the clues to a past whose allure is heightened by the fact that it has vanished. And, finally, Woodward shows us how ruins serve as the source of inspiration for the artist who sees beauty in decay and desolation; he quotes by way of example what he calls the finest sonnet Shelley ever wrote: "Round the decay/Of that colossal wreck, boundless and bare/The lone and level sands stretch far away.""--BOOK JACKET.